2018
DOI: 10.1111/mec.14796
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and population genomics of a lotic water beetle across a complex tropical landscape

Abstract: The habitat template concept applied to a freshwater system indicates that lotic species, or those which occupy permanent habitats along stream courses, are less dispersive than lentic species, or those that occur in more ephemeral aquatic habitats. Thus, populations of lotic species will be more structured than those of lentic species. Stream courses include both flowing water and small, stagnant microhabitats that can provide refuge when streams are low. Many species occur in these microhabitats but remain p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 79 publications
0
18
0
Order By: Relevance
“…The pattern found here is indeed comparable to findings by Economo et al (2015) and Jønsson et al (2014), who showed that Pheidole ant lineages and Pachycephala passerine birds, respectively, have expanded their ranges across biogeographic regions, followed by ecological filtering and a cascade pattern of dispersal from higher to lower diversity areas during these range expansions. Although ecological opportunity and taxon cycle hypotheses seem plausible explanation for the observed pattern of recent diversification associated with altitudinal shifts, we cannot exclude that it reflects the results of neutral (non-adaptive) processes (Czekanski-Moir and Rundell, 2019): spatial isolation following dispersal can also drive divergence, especially in species with low dispersal ability such as mayflies (Rutschmann et al, 2014) and in strongly structured habitat as New Guinean mountains (Janda et al, 2016;Lam et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…The pattern found here is indeed comparable to findings by Economo et al (2015) and Jønsson et al (2014), who showed that Pheidole ant lineages and Pachycephala passerine birds, respectively, have expanded their ranges across biogeographic regions, followed by ecological filtering and a cascade pattern of dispersal from higher to lower diversity areas during these range expansions. Although ecological opportunity and taxon cycle hypotheses seem plausible explanation for the observed pattern of recent diversification associated with altitudinal shifts, we cannot exclude that it reflects the results of neutral (non-adaptive) processes (Czekanski-Moir and Rundell, 2019): spatial isolation following dispersal can also drive divergence, especially in species with low dispersal ability such as mayflies (Rutschmann et al, 2014) and in strongly structured habitat as New Guinean mountains (Janda et al, 2016;Lam et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…This is the likely ancestral habitat type in Exocelina, with four subsequent shifts to lentic habitats (and only a few species in the lentic clades) (Toussaint et al 2015). Most species have limited geographic ranges; in one widespread epigean species population genomic studies revealed strong geographic structure even in populations as close to each other as 40 km straight line (Lam et al 2018). The lotic beetles often hide in the gravel when disturbed, and observations of M. Balke in New Guinea suggest that the interstitial of riverbanks is often utilized by these beetles, possibly to avoid downstream drift.…”
Section: Discussionmentioning
confidence: 97%
“…We use the standard genetic marker for molecular biodiversity assessment, the 5' end of the mitochondrial cytochrome c oxidase 1 gene (cox1 or CO1), also referred to as the "DNA barcode" (Hebert et al 2003) (also see the comprehensive background data in the BOLD Handbook under boldsystems.org for technical details). We are aware that this is only a single marker which is not related to speciation (Kwong et al 2012), with known issues for species delineation, including in Dytiscidae (Hawlitschek et al 2012;Hendrich et al 2010), but have found the approach very useful in many lineages at the species and even population level (Hendrich et al 2010;Lam et al 2018;Megna et al 2019). Careful cross checking of morphological and molecular taxonomic evidence is the foundation of our investigation.…”
Section: Discussionmentioning
confidence: 99%